Molecular biomarkers predicting early development of endometrial carcinoma: A pilot study. (14th August 2019) - Lupini, Laura; Scutiero, Gennaro; Iannone, Piergiorgio; Martinello, Ruby; Bassi, Cristian; Ravaioli, Noemi; Soave, Ilaria; Bonaccorsi, Gloria; Lanza, Giovanni; Gafà, Roberta; Loizzi, Vera; Negrini, Massimo; et al.
Abstract: Objective: Endometrial carcinoma represents the most common gynaecological cancer and the sixth most frequent cancer among women worldwide. The 5‐year survival of patients with stage I endometrial carcinoma is 75%–88% versus 50% for stage III or 15% for stage IV disease. Therefore, early detection could improve survival rates. Specifically, in the most prevalent, type 1 endometrial cancer develops from hyperplastic endometrium. The aim of the study was to evaluate the utility of cancer gene mutations from endometrial biopsies towards predicting synchronous or metachronous development of malignant lesions. The aim of the study was to evaluate whether endometrial biopsies could already carry mutations in cancer genes useful for predicting or anticipating subsequent cancer development. Methods: Patients with a previous endometrial biopsy negative for cancer, followed by a subsequent biopsy positive for cancer, were included in the study. A fifty cancer genes targeted next‐generation sequencing panel were used to investigate mutations in matched non‐cancerous and malignant samples. Results: All biopsies from cancer tissues harboured mutations in one or more of the following genes: APC, CTNNB1, FBXW7, HNF1A, KRAS, MTOR, NRAS, PIK3CA, PTEN, RB1 and TP53 . Additionally, 50% of the biopsies from matched non‐cancerous tissues exhibited mutations in PTEN, KRAS or PIK3CA genes. Conclusions: These results suggest that detecting pathogenic mutations in oncogenes or tumour suppressor genes in an otherwise benign condition is associated with a risk of developing a malignant disease. Given the identification of mutations several months or years before the appearance of a malignancy, our finding suggests that a closer monitoring of patients who present such molecular alterations in non‐cancerous uterine mass is warranted.